KEMUDAHAN DAN KEMANFAATAN PENGARUHNYA TERHADAP KEPUTUSAN PENGGUNAAN SISTEM PEMBAYARAN E-MONEY OVO, GO-PAY, DAN DANA - Rizki Aprilia Dwi Susanti; Dewi Fardahlia; Poppy Indrihastuti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2021)
The results of this study use quantitative research. Data were collected using a questionnaire of 90 respondents and the population in this study were management students at the University of Tribhuwana Tunggadewi Malang with the research sample used was purposive sampling. Data were analyzed using multiple linear regression analysis with the result that the effect of convenience partially had a significant effect on the electronic money payment system with a value of t arithmetic> t table and a significant value <0.05. The effect of partial benefit has a significant influence on the electronic money payment system with a value of t arithmetic> T table and a significant value <0.05. While simultaneously the effect of convenience, and expediency has a significant effect on the electronic money payment system by producing a significant probability value <0.05, simultaneously the ease and benefit variable has a significant effect on the electronic money payment system with case studies of ovo, go-pay users and funds to management students at the Malang Tribhuwana Tunggadewi University.